Influence of Self-Interference in a Radar System for a Correlation Based True-Speed-Over-Ground Estimation Approach - Reißland, Torsten; Michler, Fabian; Weigel, Robert; Koelpin, Alexander; Lurz, Fabian (2022 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2022, 2022)
In this paper we present an experimental examination on the influence of self-interference in a true-speed-overground measurement system. The setup is based on two antenna pairs, in which interference is to be expected if they transmit simultaneously. This work compares the estimation results for simultaneous and for time division multiplexed transmission. Furthermore, an approach for the decoupling of the receive channels is introduced and examined.
CRIS-Team Scopus Importer:2022-04-15
Keywords: correlation; interference; radar; rail transportation; velocity measurement